Changing civil society in Spain through transparency and civic technologies - Magallón-Rosa,Raúl (2017)
This paper addresses the role of open data in the development of civic technologies in Spain. We have analysed organisations that are using technology as a tool to improve transparency, democracy and citizen participation in public matters. During this research we run through the evolution of the use of technologies by civil society in Spain, we define the concept of civic technologies and propose a set of typologies, paying special attention to the source of data, with the final aim of knowing how often public open data has been used. We conclude by highlighting the need to increase the communication between public and private institutions and the organisations that use data in favour of providing useful information and making easier the development of civic technologies.